Fatigue among Cancer Patients Receiving Radiation Therapy in a Selected Hospital, Mangalore - Raju, Giya; Crasta, Glinivia Reesha; Rodrigues, Jane; Johny, Jelmol; Dsouza, Jelvita; T., Denitha (Journal of Health and Allied Sciences NU, 2022)
Introduction Cancer is a group of diseases characterized by the uncontrolled proliferation of aberrant cells. Radiation therapy is one of the cancer treatments options. It uses high-energy waves to attack tumor cells, as well as adjacent cells. The majority of cancer patients report feeling tired at the start of treatment or after a few weeks of radiation therapy. It is one of the most disabling and ongoing side effects of anticancer therapy among cancer patients. As a result, cancer-related fatigue can be a troubling symptom for most people getting anticancer treatment which is commonly underdiagnosed by the health care team. This research study aids us in assessing fatigue in cancer patients who receive radiation therapy as a treatment.Materials and Methods A quantitative descriptive research design was used in this study to collect data from 138 cancer patients who were undergoing radiation therapy both inpatient and outpatient departments of the selected Medical College Hospital in Mangaluru. The samples for this study were chosen using a purposive sampling technique. Data were collected by administering baseline proforma and Fatigue Assessment Scale.Results Majority of the patients were experiencing substantial fatigue, that is, 105 (76.08%) of patients were experiencing fatigue, 8 (5.79%) were experiencing extreme fatigue. and only 25 (18.11%) were experiencing no fatigue. Mean percentage shows that the majority, that is, 57%, of the patients with cancer experience physical fatigue and 50.25% experience mental fatigue. There is no significant association found between fatigue and selected demographic variables except for marital status (p = 0.015). Hence H0 is accepted at 0.05 level of significance, except for one selected variable.Conclusion The present study concluded that fatigue is one of the common symptoms and adverse effects experienced among cancer patients who receive radiation therapy. Health care professionals should consider the impact of fatigue on the individual and effective fatigue management to be provided to improve the quality of life
Keywords: fatigue; Fatigue Assessment Scale (FAS): IDL care foundation; radiation therapy; cancer.